Leaf nitrogen and phosphorus stoichiometry of the halophytes across China - Tong, Ran; Ma, Cong; Lou, Chenyang; Yuan, Wenwen; Zhu, Nianfu; Wang, G. Geoff; Wu, Tonggui (Frontiers in Plant Science, 2023)
Halophytes play a crucial role in the ecological restoration of saline and alkaline land and hold promising benefits to food security in China. Although a variety of aspects of halophytes have been extensively addressed, there is still a lack of overall understanding of the leaf nitrogen (N) and phosphorus (P) stoichiometric characteristics, especially at a national scale. We compiled a national dataset of 311 observations from 113 sampling sites across China to explore the changing trends and influencing factors on leaf N and P concentrations, and N:P ratio of halophytes. The results showed that leaf N concentration decreased significantly with increasing latitude (LAT), which was mainly driven by the mean annual temperature (MAT) and mean annual precipitation (MAP). The leaf P concentration increased remarkably with increasing longitude (LON), which was induced by the variation in soil total P (TP) content. The leaf N:P ratio increased as LAT increased and LON decreased, which was potentially regulated by the MAT, MAP, and soil TP content. The scaling exponents of the N-P relationship differed significantly among halophyte types and were 0.40, 0.87, and 1.39 for euhalophyte, pseudohalophyte, and recretohalophyte, respectively. The leaf N concentration exhibited significant differences among ecosystem types and halophyte types, whereas the leaf P concentration and N:P ratio remained relatively stable. In summary, the leaf N concentration and N-P scaling exponent might be the classification criteria for halophyte types from the perspective of plant nutrient resource allocation. Moreover, this study characterized the spatial distribution and allocation strategy of leaf N and P stoichiometry in halophytes by data integration analysis, providing the basic information for nutrient management in the processes of the future domestication and introduction of halophytes.